2001
DOI: 10.1074/jbc.m006840200
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Unfolding of Bombyx mori Glycyl-tRNA Synthetase

Abstract: Unfolding of Bombyx mori glycyl-tRNA synthetase was examined by multiple spectroscopic techniques. Tryptophan fluorescence of wild type enzyme and an N-terminally truncated form (N55) increased at low concentrations of urea or guanidine-HCl followed by a reduction in intensity at intermediate denaturant concentrations; a transition at higher denaturant was detected as decreased fluorescence intensity and a red-shifted emission. Solute quenching of fluorescence indicated that tryptophans become progressively so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…1). The shifting of max to a longer wavelength was similar to other reported unfolding proteins such as concanavalin A, methanol dehydrogenase, and glycyl-tRNA synthetase, indicating a conformational change of tryptophan residues from an apolar to a polar environment (Wang et al, 2000;Dignam et al, 2001;Chatterjee and Mandal, 2003). With a series of intensity ratio between 330 and 350 nm representing native and unfolded conformations, an unfolding curve was then established as a function of the denaturant (Fig.…”
Section: Steady-state Unfolding and Transitional Free Energy Analysissupporting
confidence: 80%
“…1). The shifting of max to a longer wavelength was similar to other reported unfolding proteins such as concanavalin A, methanol dehydrogenase, and glycyl-tRNA synthetase, indicating a conformational change of tryptophan residues from an apolar to a polar environment (Wang et al, 2000;Dignam et al, 2001;Chatterjee and Mandal, 2003). With a series of intensity ratio between 330 and 350 nm representing native and unfolded conformations, an unfolding curve was then established as a function of the denaturant (Fig.…”
Section: Steady-state Unfolding and Transitional Free Energy Analysissupporting
confidence: 80%
“…Others studying proteins that unfold via an equilibrium intermediate (eg. [27] ) have observed that refolding of partially unfolded protein is not fully reversible. In the present case, samples of RXR LBD incubated in 2.5M guanidine overnight showed visible signs of aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…2) using GraphPad Prism 5.0.Where S obs is the observed spectroscopic signal, S N and S U are the signals for the native and unfolded species, respectively, ΔG is the free energy of unfolding in the absence of denaturant, m is the partial derivative of ΔG with respect to denaturant, and d is the concentration of denaturant. S obs and d are the dependent and independent variables; S N , S U , ΔG, and m are treated as fitting parameters [48]. The C m , the GdnHCl concentration at the midpoint of GdnHCl-induced unfolding curve, was obtained using the following equation (Eq.…”
Section: Methodsmentioning
confidence: 99%